Presenting Successful Wildlife Education Programs— The Message - Lord, Jeannie (Wildlife Rehabilitation Bulletin, 2006)
The development of a successful formal wildlife educational outreach program is contingent on many factors. As important as punctuality, dress, preparation, and educational aides are to the totality of a wildlife educational outreach program, it is the message communicated that is the breadth and soul of the program.